Voting Scores for Members of the United States Congress, 1945-1982 ([Verlag nicht ermittelbar], 1984)
This data collection contains voting scores taken from the CONGRESSIONAL QUARTERLY ALMANAC, a publication of Congressional Quarterly, Inc. (CQ) for the years 1945 to 1982 (79th-97th Congresses). Part 1 contains voting scores for members of the United States Senate, and Part 2 contains such scores for the members of the United States House of Representatives. In both parts, the unit of analysis is the individual member of Congress. The identification variables in each file include member name, member's state, and member's party. In most instances a set of scores is presented for each member of Congress, for each session of the Congress, and for the Congress as a whole (both sessions). For the 96th and 97th Congresses (1979-1980, 1981-1982) scores for both sessions combined are not provided. The major types of CQ voting scores in the data collection are: (1) "voting participation score," indicating member's attendance (not to be confused with the CQ "on the record" score which shows how often the member has taken a stand on all issues), (2) "partisan voting score," calculated on a subset of the total roll calls that CQ designated as "party unity" roll calls, e.g., roll calls in which a majority of voting Democrats opposed a majority of voting Republicans (with exceptions in the 83rd and 88th Congresses when a "party voting" score was released), (3) "bipartisan voting score," consistently figured by CQ on a subset of the total bipartisan roll calls, i.e., those in which a majority of Democrats and a majority of Republicans voted the same way (until 1978 when the score was no longer reported), (4)"conservative coalition score," based on a subset of roll calls in which a majority of voting Southern Democrats and a majority of voting Republicans opposed the position of a majority of voting Northern Democrats, (5) "presidential issues score," which rates members on those roll calls dealing with issues on which the president has clearly and previously stated a personal position (from 1955 to 1970, this score was further subdivided into support scores for foreign and for domestic policies of the president), (6) "federal role score," which gauges the Congressperson's support and opposition of moves for a larger or smaller federal role (in earlier Congresses, CQ used a similar process to figure "economy support," opposition scores that were designed to represent a member's position on moves to limit or increase federal spending), and (7) a set of interest group scores taken from the CQ WEEKLY REPORTS and added to the two data files (for the years 1960 to 1982) that score each Congressperson's support of interest groups, i.e., Americans for Democratic Action (ADA), the Americans for Constitutional Action (ACA), the Committee on Political Education (COPE), and the National Farmers Union (NFU). Interest group ratings are included only for each session, not for the entire Congresses. (Beginning with the 1978 session, NFU rating scores were no longer included.)